2019
DOI: 10.1111/irv.12672
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Global Influenza Surveillance and Response System for global respiratory syncytial virus surveillance—opportunities and challenges

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Wheezing, rhinitis and tachypnoea seem like notable additional clinical signs associated with RSV-positivity in children, as already described in a previous study [ 16 ], and would need to be included in a second pilot study to fully assess their relevance in increasing the case definition sensitivity. Extending the case definition to include other symptoms such as sepsis and apnoea might also need to be considered for children < 6 months, as recommended in WHO documents for RSV surveillance [ 10 , 14 , 15 ]. This would probably allow to better address the severity of disease caused by RSV in this age group, as these symptoms might be more frequently associated to severe forms [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheezing, rhinitis and tachypnoea seem like notable additional clinical signs associated with RSV-positivity in children, as already described in a previous study [ 16 ], and would need to be included in a second pilot study to fully assess their relevance in increasing the case definition sensitivity. Extending the case definition to include other symptoms such as sepsis and apnoea might also need to be considered for children < 6 months, as recommended in WHO documents for RSV surveillance [ 10 , 14 , 15 ]. This would probably allow to better address the severity of disease caused by RSV in this age group, as these symptoms might be more frequently associated to severe forms [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our usual SARI case definition, based on the WHO SARI case definition, was used: acute respiratory infection with fever ≥ 38 °C (or history of fever reported by the patient) and cough or dyspnoea, with onset of symptoms within the past 10 days, and requiring hospitalisation (minimum overnight). However, in order to align with one of the case definitions proposed in WHO’s RSV strategy document [ 14 , 15 ], the participating hospitals were recommended to be flexible over the fever criteria, meaning that patients without fever but meeting the other criteria could also be included.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the WHO is performing a pilot study which aims to test whether it is feasible to make use of the Global Influenza Surveillance and Response System platform for RSV surveillance without adversely affecting the well-established ILI and SARI surveillance of influenza [30]. The first results of this pilot are encouraging and even indicated that combining RSV and influenza surveillance can be an advantage to the current influenza surveillance systems [31].…”
Section: Discussionmentioning
confidence: 99%
“…All laboratories successfully achieved a 100% correct score 13. RSV Reference Laboratories functioned according to Terms of Reference developed by the WHO Global Influenza Program and the WHO Global RSV Surveillance 13,14…”
Section: Methodsmentioning
confidence: 99%